Community-Acquired Serratia Marcescens Spinal Epidural Abscess in a Patient Without Risk Factors: Case Report and Review - Michael D Parkins; Daniel B Gregson (Canadian Journal of Infectious Diseases and Medical Microbiology)
Serratia marcescens has rarely been reported as an agent of invasive disease in patients presenting from the community. Furthermore, S marcescens is frequently opportunistic, affecting individuals with serious medical comorbidities including immune suppression and diabetes. A case of a community-acquired S marcescens spontaneous lumbar epidural abscess presenting as cauda equina syndrome is reported in a previously well 36-year-old man with no identifiable risk factors. To the authors’ knowledge, this is the first report of invasive S marcescens causing disease in a patient with no medical comorbidities.